Annealing behaviour of charge collection of neutron irradiated diodes from 8-inch p-type silicon wafers - Kałuzińska, Oliwia Agnieszka; Diehl, Leena; Sicking, Eva; Mühlnikel, Marie Christin; de Almeida, Pedro Gonçalo Dias; Kieseler, Jan; Kettner, Matthias; Walter, David; Defranchis, Matteo M. (Journal of Instrumentation, 2025)
To face the higher levels of radiation due to the 10-fold increase in integrated luminosity during the High-Luminosity LHC, the CMS detector will replace the current Calorimeter Endcap (CE) using the High-Granularity Calorimeter (HGCAL) concept. The electromagnetic section as well as the high-radiation regions of the hadronic section of the CE will be equipped with silicon pad sensors, covering a total area of 620 m2. Fluences up to 1.0·1016 neq/cm2 and doses up to 2 MGy are expected considering an integrated luminosity of 3 ab-1. The whole CE will normally operate at -35°C in order to mitigate the effects of radiation damage. The silicon sensors are processed on 8-inch p-type wafers with an active thickness of 300 μm, 200 μm and 120 μm and cut into hexagonal shapes for optimal use of the wafer area and tiling. With each main sensor several small sized test structures (e.g. pad diodes) are hosted on the wafers, used for quality assurance and radiation hardness tests. In order to investigate the radiation-induced bulk damage, 28 diodes have been irradiated with reactor neutrons at the TRIGA reactor in JSI (Jožef Stefan Institute, Ljubljana) to 13 fluences between 6.5·1014 neq/cm2 and 1.5·1016 neq/cm2. The charge collection of the irradiated silicon diodes was determined through transient current technique (TCT) measurements. The study focuses on the isothermal annealing behaviour of the bulk material at 60°C. The results have been used to extend the usage of thicker silicon sensors in regions expecting higher fluences and are being used to estimate the expected annealing effects of the silicon sensors during year-end technical stops and long HL-LHC shutdowns currently foreseen with a temperature around 0°C.